- Translation 2 units down
- g(x) = 3f(x)
Further explanation
Translation and stretching are forms of geometrical transformation.
Given c ∈ R, after the transformation coordinates of each point, (x, y) on the graph of y = f(x) change as follows:
Horizontal shift
- function: [tex]\boxed{ \ y = f(x + c) \ }[/tex] translation c units left
- coordinates: [tex]\boxed{ \ (x - c, y) \ }[/tex] translation c units left
Vertical shift
- function: [tex]\boxed{ \ y = f(x) + c \ }[/tex] translation c units up
- coordinates: [tex]\boxed{ \ (x, y + c) \ }[/tex] translation c units up
Horizontal stretch
- function: [tex]\boxed{ \ y = f(cx) \ }[/tex] horizontal stretch by a factor of c
- coordinates: [tex]\boxed{ \ (\frac{x}{c}, y) \ }[/tex] horizontal stretch by a factor of c
Vertical stretch
- function: [tex]\boxed{ \ y = cf(x) \ }[/tex] vertical stretch by a factor of c
- coordinates: [tex]\boxed{ \ (x, cy) \ }[/tex] vertical stretch by a factor of c
- - - - - - - - - -
Problem No.1
[tex]\boxed{ \ f(x) = 4x + 9 \ } \rightarrow \ ? \rightarrow \boxed{ \ g(x) = 4x + 7 \ }[/tex]
Clearly, to obtain the graph of [tex]\boxed{ \ g(x) = 4x + 7 \ }[/tex] we shift the graph of [tex]\boxed{ \ f(x) = 4x + 9 \ }[/tex] downward 2 units.
- [tex]\boxed{ \ f(x) = 4x + 9 \ }[/tex] translation 2 units down.
- [tex]\boxed{ \ f(x) = (4x + 9) - 2 \ }[/tex]
- [tex]\boxed{ \ g(x) = 4x + 7 \ }[/tex]
Thus. the transformation that takes the graph [tex]\boxed{f(x) = 4x + 9}[/tex] to the graph [tex]\boxed{g(x) = 4x + 7}[/tex] is the translation 2 units down.
- - - - - - - - - -
Problem No.2
[tex]\boxed{ \ f(x) \ } \rightarrow \ ? \rightarrow \boxed{ \ g(x) = 3f(x) \ }[/tex]
Clearly, to obtain the graph of [tex]\boxed{ \ g(x) = 3f(x) \ }[/tex] we stretch vertically the graph of [tex]\boxed{ \ f(x) \ }[/tex] by a factor of 3 (multiply each y-coordinate by 3).
Thus. the equation describes function g is [tex]\boxed{ \ g(x) = 3f(x) \ }[/tex], that is, a vertical stretch of the graph of function f by a factor of 3.
Learn more
- Which phrase best describes the translation from the graph y = 2(x – 15)² + 3 to the graph of y = 2(x – 11)² + 3? https://brainly.com/question/1369568
- Which equation represents the new graph? https://brainly.com/question/2527724
- What transformations change the graph of (f)x to the graph of g(x)? https://brainly.com/question/2415963
Keywords: what transformation, takes, the graph, f(x) = 4x + 9, g(x) = 4x + 7, which, the equation, describes, function g, horizontal, vertical, stretch, transformation geometry, translation, units, down, factor